1986
DOI: 10.1104/pp.80.1.34
|View full text |Cite
|
Sign up to set email alerts
|

A Group Translocator for Sucrose Assimilation in Tonoplast Vesicles of Sugarcane Cells

Abstract: ABSTRACIExistence of a group translocator for sucrose transfer into vacuoles of sugarcane (Saccharum sp.) cells has been further confirmed by the use of tonoplast vesicles isolated from intact vacuoles. The group translocator depends on external UDP-Glucose (Glc) and, via a series of enzymic reactions within the tonoplast, sucrose phosphate and sucrose are deposited inside the vesicles. Fructose-6-phosphate was not required for UDPGic uptake, nor was it taken up. None of the other supr phosphates tested were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…Maretzki and Thom (16,20) have presented the strongest evidence that sucrose must be cleaved and resynthesized for transport into sugarcane, although the presence of a group transporter has recently been questioned (17,18). The data presented here also would seem to be in conflict with their initial data.…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…Maretzki and Thom (16,20) have presented the strongest evidence that sucrose must be cleaved and resynthesized for transport into sugarcane, although the presence of a group transporter has recently been questioned (17,18). The data presented here also would seem to be in conflict with their initial data.…”
Section: Resultscontrasting
confidence: 58%
“…However, the ratio of labeled glucose to fructose in sucrose in the storage compartment was low in all tissues, indicating less than 15% randomization of label. The group transporter hypothesis of Maretzki and Thom (16,20) requires complete randomization for uptake into the vacuole, since they have reported that ['4C]fructose was not taken up by isolated vacuoles, but required conversion through UDPG for transport. In this study, however, although some randomization of label was observed in sucrose from ethanol extracts, it was not nearly enough to substantiate a requirement for sucrose cleavage and resynthesis during transport.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the specific enzyme in plants probably indicates its importance in sucrose synthesis (9), but it could also be involved in the transport of sucrose, particularly in sugarcane and red beet storage tissues (14,18,19), where a group translocator has been postulated to operate. Our results showing the enzyme to be present in vacuole preparations from storage tissues support the view that sucrose phosphatase could participate in their sucrose transport.…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose, maltose, melezitose, turanose, Pi, PPi, and F-cause inhibition of activity. Sucrose phosphate had been suggested as an intermediate in sucrose transport across the tonoplast in some plants (3,6,8) and recent evidence strongly supports the involvement of sucrose phosphate in a group translocation mechanism for sucrose transfer into isolated vacuoles of both sugarcane and red beet and into tonoplast vesicles of sugarcane (14,18,19). UDPGlucose was the external substrate for the group translocator and sucrose and sucrose phosphate with or without added MgATP were not taken up by the sugarcane vacuoles or vesicles (14,18).…”
mentioning
confidence: 94%